Development of the Learning Module Book of English for Specific Purposes Course to Realize Relevance and Meaningfulness - Carla Sih Prabandari; Gregorius Punto Aji (Indonesian Journal of English Language Studies (IJELS), 2019)
This research aims to develop Learning Moduls that support a learning model designed to integrate the theory and the implementation in which relevance and meaningfulness of English for Specific Purposes (ESP) course can be achieved. Therefore, the problem of this research is: What kind of learning module book of English for Specific Purposes course to realize relevance and meaningfulness? This research used Research and Development method that aims to develop and validate products in education. Steps of development method that will be used include (1) collecting pre-development data, (2) designing the product prototype, (3) verifying the product to experts who are competent at the product, (4) revising the product into the product prototype 2, (5) applying the product for obtaining qualitative evaluation, and (6) revising the product into the final product that has been validated after having steps of expert verification and implementation. The research data were qualitative and quantitative data that had been verified by experts and evaluated by students in terms of how the product designed can realize relevance and meaningfulness of the integration between theories and real implementation. The development research result is in accordance with the objective in which the result is an ESP learning module book for students of English Language Education Study Program of Sanata Dharma University.